Is the MIND diet useful for polycystic ovary syndrome? A case-control study - Mina Darand; Narges Sadeghi; Zahra Salimi; Mahlagha Nikbaf-Shandiz; Asieh Panjeshahin; Hawal Lateef Fateh; Mahdieh Hosseinzadeh (BMC, 2024)
Abstract Background Polycystic ovary syndrome (PCOS) is the most prevalent cause of ovulatory infertility and endocrine abnormalities in reproductive-age women. Although the MIND diet has been introduced to improve brain function, evidence shows that the MIND diet is rich in beneficial food groups that can have a preventive effect on other metabolic disorders. The present study was conducted to investigate the association between adherence to the MIND diet and PCOS. Methods This age and BMI frequency-matched case-control study was conducted on 216 women between January 2018 and March 2019 in Yazd, Iran. PCOS was diagnosed based on Rotterdam criteria. Participants were selected by convenience sampling method. The validated 178-item food frequency questionnaire was used to assess the usual dietary intake. Logistic regression was used to estimate the association between the MIND diet and PCOS. Results The findings of the present study showed a significant inverse association between adherence to the MIND diet and PCOS in the crude model (OR for T3 vs. T1: 0.12 (95% CI: 0.05-0.25), P-value < 0.001) and multivariable-adjusted model including energy intake, age, BMI, waist circumference, marital status, pregnancy history, drug use history, education and physical activity (OR for T3 vs. T1 = 0.08 (95% CI: 0.03-0.19), P-value < 0.001). Adherence to the MIND diet had a protective effect of 92%. Conclusion Although the results of the present study showed that higher adherence to the MIND diet is associated with a lower risk of PCOS, more studies are needed to confirm these findings in the future.